Visualization and cognitive graphics in scientific research; PalArch's Journal of Archaeology of Egypt/Egyptology; Vol. 17, iss. 10 - Berestneva O. G. Olga Grigorievna; Lyzin I. A. Ivan Alexandrovich; Sharopin K. A. Konstantin Aleksandrovich; Berestneva E. V. Elena Viktorovna; Polisadova A. I. Alena; Petrova L. A. Lyudmila; Stepanenko N. P. Nina Petrovna (2020, 2020)
Title screen